Experimental Research on Mechanical Properties of Apple Peels - Wang Juxia; Cui Qingliang; Li Hongbo; Liu Yaping (Institute for Research and Community Services, Institut Teknologi Bandung, 2015)
Knowledge of the mechanical properties of apple peel, as the outermost tissue of the fruit, is crucial for the designing of apple harvesting machines. In this study, longitudinal and transverse tensile tests were conducted on peels from the shadow side and sunlit side of two apple cultivars (Starkrimson and Fuji) using an electronic universal testing machine, and tear tests and puncture tests were carried out on peels of both sides as well. The stress-strain curves and tear and puncture force-deformation curves of the peels were acquired and the tensile strength, elastic modulus, failure strain tear strength, puncture strength of the peels were measured. Also, scanning electron microscope images were made. The results showed that the maximum values of tensile strength, elastic modulus, fracture strain, tear strength, and puncture strength were 2.56 MPa, 24.00 MPa, 19.92%, 0.391 kN·m-1, and 0.289 N·mm-2, respectively. The tensile strength, elastic modulus, and puncture strength values for the Starkrimson peels were higher than those for the Fuji peels from the same side. Apple peel is an anisotropic heterogeneous material. The bearing capacity of the peel depends on the number and distribution of microcracks on the surface, and the size and shape of the epidermal cells. The organization and connections between the cells determine the strength of the connections between cells.